The performance of stability test using Bantak aggregate and AC50/70 as polymer on Marshall characteristic - Tino Putro Pangestu; Wasiu Akande Ahmad; Adi Setiabudi Bawono; Mohamad Aqifd (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
This study aims to determine Marshall's characteristics using asphalt binder modified polymer AC 50/70 (Starbit E-55) using local Bantak material. The test method used is a hot mix asphalt (Hot Mix) with the Marshall method. The asphalt content used was 5% successively; 5.5%; 6%; 6.5%; and 7% consisting of 3 specimens for each variant. The research was carried out at the Material Laboratory of the Department of Civil Engineering and Planning, Faculty of Engineering, Yogyakarta State University. The results of the Marshall characteristic performance test at the Optimum Asphalt Level (KAO) 6.5% are as follows: Marshall stability mean value is 1197.6 kg, Density mean value is 2.34 gr/cc, the mean value of melt (Flow) is 3, 1 mm, the mean value of VIM (Void in Mix) was 4.83%, the mean value of VMA (Void in Mineral Aggregate) was 13.40%, the mean value of VFB (Void Filled Bitumen) was 60.61%, and the mean value of MQ (Marshall Quotient) 391.08 kg/mm.